Sustainable integration of digitalisation in nursing education—an international scoping review - Tischendorf, Tim; Heitmann-Möller, André; Ruppert, Sven-Nelson; Marchwacka, Maria; Schaffrin, Sandra; Schaal, Tom; Hasseler, Martina (Frontiers in Health Services, 2024)
Trainees and teachers at nursing schools as well as nursing professionals are increasingly facing new challenges as a result of the digital transformation. Opportunities for the entire care system exist in the improvement of care quality and communication between those involved. However, this change also harbours risks, such as the use of immature digital applications in the care sector, data theft and industrial espionage. In order to be able to exploit the potential of digitalisation despite these risks, it is necessary to integrate relevant aspects such as digital skills into nursing training. The aim of this study is to investigate the extent to which the sustainable integration of digitalisation in nursing education is discussed.The methods of the systematic literature and database search were carried out in the form of a scoping review according to the PRISMA scheme. The PubMed and CINAHL databases were used for this purpose. The search period covered the years 2017 to 2023.Findings: After screening the titles and abstracts using inclusion and exclusion criteria, 13 studies were included in the synthesis of findings. The international literature focuses on content areas that highlight trends in digitalisation-related training in nursing. These focal points include concept development, considering the heterogeneity of demand constellations, as well as the reflexive reorientation of existing competences, whereby the technological competence of teachers is not disregarded. Other focal points relate to the initiation of digital skills in training and maintaining the employability of older nursing staff through professional development.Discussion: The literature research shows that there is a rudimentary discussion about digitalisation and curricular developments in nursing training in an international context, while the discourse in the German-language literature is less advanced. Among the sustainability desiderata derived from the literature is the involvement of nursing professionals in the development, testing and implementation of digital technologies. Only through active cooperation between nursing professionals and nursing sciences can the topic of digitalisation be integrated into the education and training of professional nursing in a targeted and futureoriented manner, whereby the focus should always be on the ability to deal with digital technologies and the associated change.